Verificação de tipos de dosadores de sementes de milho e soja no norte do Paraná - Schmalz, Cassiano Ricardo (2014)
The first works with Precision Agriculture in Brazil started with greater intensity from the 2000s in order to know and correct soil fertility. After long years of public-private research generated a vast database of information demonstrating that activities like sowing has become an essential step. Thus, studies on the accuracy in the distribution of seeds and seed distribution in variable density and quality of sowing methods by coefficient of variation (CV) and accuracy rate (IP), have become important tools to increase productivity. To this end, we performed a case study of the performance of types of corn and soybeans seed feeders in northern Paraná, 02 models of pneumatic seeder and 05 mechanical models (honeycomb disc). The experiments conducted during 7 years in 61 different locations, by the technical department of Pioneer Seeds, quantified the losses from failures of seeds in the row. Pneumatic seeders present numerical and statistical superiority both in the soybean as corn.